(untitled) (Journal of Global Accounting, 2024)
The main objective of this study is to examine the effect of capital structure on the economic performance of listed consumer goods firms in Nigeria. The specific objectives are to ascertain the effect of the Debt-to-Equity Ratio, Debt-to-Capital Ratio, on Cash Flow Return on Investment (CFROI) of these firms. Data were collected from a sample of fourteen consumer goods firms from 2014 to 2023. Hypotheses were tested using Panel Estimated Generalized Least Squares. The findings revealed that the Debt-to-Equity Ratio significantly and negatively affects CFROI; whereas the Debt-to-Capital Ratio positively and significantly affect CFROI, , all at the 5% significance level. In conclusion, a balanced and strategic approach to leveraging debt, coupled with maintaining strong operational earnings, is crucial for enhancing the economic outcomes of these firms. The study recommends that financial managers of listed consumer goods firms in Nigeria should aim to reduce their debts-to-equity ratio by seeking alternative financing options such as equity financing or retained earnings, as this can help decrease financial risk and improve cash flow stability, enhancing overall economic performance.